Learning of Tanggomo Local History To Improve Students' Critical Thinking Skills - Mahmud, Djulia Indriani A.H (HISTORIKA, 2020)
Abstrack        This article discusses about the relevance of local history and  lcritical thinking skills. Learning history today experiences many fundamental problems, including a lack of critical thinking skills. Which ultimately impact on learning that is boring, and not interesting. Though history learning should emphasize the learning process on philosophical and scientific meaning. Because learning history is not just a learning, but also a scientific discipline. Integrating local history into history learning is intended to enhance the analytical abilities and critical abilities of students in identifying local events where they live. The method used in writing this is the literature review method.